A Comprehensive and Comparative Study on the Biochemical Composition and Non-Volatile Taste Compounds of Thirteen Shellfish Species - Long Li; Zhiyu Fu; Yujun Liu; Zhiyuan Song; Xinrui Yang; Di Yu; Qingzhi Wang; Hai Chi; Jie Zheng (Foods)
This study aimed to systematically investigate and compare the biochemical composition of 13 locally abundant shellfish species (Dalian, China) and the taste characteristics of these shellfish and their boiling liquids. The results showed that Chlamys farreri exhibited the highest level of protein (64.58%) and polyunsaturated fatty acids (53.84% of total fatty acids), whereas Scapharca subcrenata showed a better composition and proportion of essential amino acids (EAA/TAA = 39.02%, EAA/NEAA = 63.98%) compared to other species. Glu, Gly, Ala, Arg, 5′-monophosphate (GMP), lactic acid, succinic acid, and malic acid were quantitatively determined as the main taste compounds in shellfish and their boiling liquids. The equivalent umami concentration (EUC) values, reflecting the synergistic effect of umami compounds, showed distinct characteristics, and the maximum umami intensities were found in Meretrix meretrix (586.8 g monosodium glutamate (MSG)/100 g) and the boiling liquid of Clinocardium californiense (358.3 g MSG/100 g), respectively. Based on these experimental results, C. californiense was found to have the highest prehensive quality score as revealed by principal component analysis (PCA). These results are important for promoting studies aimed at nutritional value development and taste compounds improvement of these shellfish species, especially for flavor enhancer development. Meanwhile, different shellfish species can be comprehensively developed and utilized based on their distinct nutritional properties, and this would translate into greater profitability for producers.